Promoting Graduate Student Mental Health During COVID-19: Acceptability, Feasibility, and Perceived Utility of an Online Single-Session Intervention - Wasil, Akash R.; Taylor, Madison E.; Franzen, Rose E.; Steinberg, Joshua S.; DeRubeis, Robert J. (Frontiers in Psychology, 2021)
The COVID-19 outbreak has simultaneously increased the need for mental health services and decreased their availability. Brief online self-help interventions that can be completed in a single session could be especially helpful in improving access to care during the crisis. However, little is known about the uptake, acceptability, and perceived utility of these interventions outside of clinical trials in which participants are compensated. Here, we describe the development, deployment, acceptability ratings, and pre-post effects of a single-session intervention, the Common Elements Toolbox (COMET), adapted for the COVID-19 crisis to support graduate and professional students. Participants (n = 263), who were not compensated, were randomly assigned to two of three modules: behavioral activation, cognitive restructuring, and gratitude. Over one week, 263 individuals began and 189 individuals (72%) completed the intervention. Participants reported that the intervention modules were acceptable (93% endorsing), helpful (88%), engaging (86%), applicable to their lives (87%), and could help them manage COVID-related challenges (88%). Participants reported pre- to post-program improvements in secondary control (i.e., the belief that one can control their reactions to objective events; dav=0.36, dz=0.50, p<0.001) and in the perceived negative impact of the COVID-19 crisis on their quality of life (dav=0.22, dz=0.25, p<0.001). On average, differences in their perceived ability to handle lifestyle changes resulting from the pandemic were positive, but small and at the level of a nonsignificant trend (dav=0.13, dz=0.14, p=0.066). Our results highlight the acceptability and utility of an online intervention for supporting individuals through the COVID-19 crisis.